Peningkatan Kemampuan Membaca Permulaan Melalui Permainan Kartu Kata - Ati Sutiati (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2020)
This study aims to (1) to describe how the use of word card games in odd semester 1 grade students at SDN 3 Selaraja, Kecamatan Warunggunung, Kabupaten Lebak, Academic Year 2017/2018 and to improve the reading ability of Indonesian Language Beginners in grade 1 elementary school students. This research is a Classroom Action Research conducted in 2 cycles with 3 meetings per cycle with a total of 27 students. In pre-action the percentage of students completeness reached 30%, after the action in cycle I the percentage of students completeness increased to 70%, in cycle II it increased to 90% so that the study did not proceed to cycle III.